(untitled) (CAHIERS MAGELLANES-NS, 2024)
while the majority, comprising 81.6%, exhibited a low level of understanding. Additionally, 15.9% ofthe participants fell within the medium level category. These findings suggest a notable disparity in thelevels of knowledge and awareness among the adult population in KSA regarding HSCT for sickle celldisease, there is also about 63% have heard about HSCT and only 37% reported never hearing about it.Conclusion: HSCT serves as a crucial remedy for severe medical conditions. In Saudi Arabia, there isa pressing demand for donors due to prevalent diseases such as sickle cell disease. Almost 63% of ourstudy participants have heard about HSCT for SCD and 37% did not hear. Further, only 58.6% of ourstudy participants are willing to donate, a percent must be increased to match the real need for HSCT.National education programs must be directed to medical schools as well as the general population toincrease awareness about HSCT, which may lead to a better attitude and willingness for HSCT donation.